SIMULATION OF MULTIMODAL TRANSPORT WITH ANYLOGIC: SIMULATION OF MULTIMODAL TRANSPORT WITH ANYLOGIC - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The application of a logistical approach has an impact on transport policy with regard to the development of freight transport systems. It is expressed in the possibility to increase the efficiency of the functioning of both the individual transport industries and the individual transport enterprise, as well as their integration [2]. In essence, combined transport is an effective integration of different modes of transport, ie. of individual transport operators and infrastructure companies in the context of the transport logistics chain. It is also known as intermodal or multimodal transport (MT).